(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The management of the exchange rate of the most important tools of economic policy because of its wide area in achieving stability and economic growth through the provision of stability in the exchange rate of the currency of the country concerned , as well as the impact and influence of money supply and then treat the economic crisis monetary and reduce the risk of currency exchange rate .For the management of the exchange rate in Iraq has passed through several stages , from installation to link to a basket of currencies to float freely , and we are dealing with in this research regard to the achievements of monetary policy , especially after the enjoyment of independence on according to the Iraqi Central Bank Law No. 56 of 2004 and Mahakgah free exchange rate of economic gains as well as the auction of foreign currency , which has had a direct impact on the stability of the Iraqi dinar exchange , as well as a Low inflation , but it is not possible to continue to manage the exchange rate through the channel of the currency auction after it has exhausted benefits in the latter currency stability and low levels of inflation , and the search for another method is consistent with the current conditions of the Iraqi economy .